Kiss by kiss a counting book for families = Ocêtôwina : peyak ôskân ohcih - akitâh-masinahikan - Van Camp, Richard 1971- (Orca Book Publishers, 2018)
"Count your kisses with baby in this delightful dual-language rhyming board book, written in English and Plains Cree."--
Place of publication taken from publisher's website
On board pages
Keywords: Zählen; Counting / Juvenile literature; Board books; Bilingual books; Board books / Juvenile literature; Bilingual books / Juvenile literature; Cree language materials / Juvenile literature; Counting; Picture books; Juvenile works; Cree language materials / Bilingual; Bilderbuch; Kinderbuch